2022
DOI: 10.1186/s13007-022-00910-1
|View full text |Cite
|
Sign up to set email alerts
|

Improved wood species identification based on multi-view imagery of the three anatomical planes

Abstract: Background The identification of tropical African wood species based on microscopic imagery is a challenging problem due to the heterogeneous nature of the composition of wood combined with the vast number of candidate species. Image classification methods that rely on machine learning can facilitate this identification, provided that sufficient training material is available. Despite the fact that the three main anatomical sections contain information that is relevant for species identificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Additionally, we will introduce classification models, such as multi-view CNN [49], which treat multiple views of an object as the same object for classification to avoid the problem of treating different projections of the same object as separate entities. For example, Silva et al [50] achieved 95% accuracy in tree species classification by using microscopic images of three major anatomical parts of wood and combining them with the multi-view random forest model, which is different from the traditional approach of using cross-sectional images alone. In future research, we will explore the optimal combination of multi-view images and the multi-view classification model, along with the point cloud data that are currently in use, to further investigate the upper limit of the classification of tree species using multi-view projection images, which can be obtained quickly and conveniently.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we will introduce classification models, such as multi-view CNN [49], which treat multiple views of an object as the same object for classification to avoid the problem of treating different projections of the same object as separate entities. For example, Silva et al [50] achieved 95% accuracy in tree species classification by using microscopic images of three major anatomical parts of wood and combining them with the multi-view random forest model, which is different from the traditional approach of using cross-sectional images alone. In future research, we will explore the optimal combination of multi-view images and the multi-view classification model, along with the point cloud data that are currently in use, to further investigate the upper limit of the classification of tree species using multi-view projection images, which can be obtained quickly and conveniently.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies trained microscopic images of the three sections and then identified the test images [ 1 , 34 ]. Here, we explored the impact of different multiples on identification results and feature visualization.…”
Section: Methodsmentioning
confidence: 99%
“…Illegal logging is the most profitable natural resource crime over the world. The financial value of illegal logging and related trade is approximately $52 to $157 billion per year [ 1 ]. Therefore, the international community has emphasized the Convention on International Trade in Endangered Species of Wild Fauna and Flora (CITES) to ban or restrict trade in endangered tree species to combat illegal logging and related trade [ 2 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the field of microscopy image analysis, traditional image processing and classical machine learning techniques have been widely employed to process and analyse images with varying signal‐to‐noise ratios and resolutions. Applications include quantifying tissue and cell numbers and hypocotyl sizes (Campbell et al ., 2017 ; Hall et al ., 2016 ), stomata and pavement cell quantification of leaves (Jayakody et al ., 2017 ; Möller et al ., 2017 ), root visualization and quantification (Yamaura et al ., 2022 ), and woody species classification (Rosa da Silva et al ., 2017 , 2022 ). Over the past decade, deep learning has emerged as a rapidly growing technology in plant microscopic imaging.…”
Section: Artificial Intelligence‐based Analysis Opens New Avenues For...mentioning
confidence: 99%